The Role of the Local Community in Sustainable Cultural Tourism - Afouxenidi, Elena (My University, 2022)
Although community involvement in sustainable practices is an issue of particular concern in the scientific field, it is not yet clear how residents can make a significant contribution towards sustainable tourism. Drawing from qualitative research in the archaeological site of Philopappos in Athens, this chapter aims to investigate residents’ perceptions of sustainable development as well as their role in sustainability within the cultural tourism context. In addition, data from field observations, published articles and archival material were used to support the findings. The study findings reveal that the residents are involved in issues of protection of the natural and cultural landscape, a fact that has led at times to a conflict with the public authorities. Overall, inhabitants can reduce the possible negative impacts of site exploitation with their involvement in the decision-making process of cultural tourism development as they have knowledge and experience of the area where cultural sites are located. The chapter concludes with a discussion of theoretical and practical implications.
Keywords: Philopappos; Residents; Cultural tourism